United States : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper on the United States of America examines the recent US labor force penetration rate (LFPR) dynamics. LFPR dynamics can be driven by structural factors and cyclical ones related to job prospects. With participation rates for older workers lower than for prime age workers, demographic models suggest that aging of the baby boom generation explains about 50 percent of the near 3p.p. LFPR decline during 2007-2013. State-level panel regression analysis is used to tie down the cyclical effect, which is estimated to account for about 30-40 percent of the decline. Significant remaining slack in the labor market points to an important role for macroeconomic and labor supply policies. This suggests a still important role for stimulative macroeconomic policies to help reach full employment. Macroeconomic policy should remain accommodative for a while given sizeable labor market slack. This slack goes beyond that signaled by the unemployment rate and takes account of the LFPR being below trend and many employees working part time 'involuntarily'.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet